2018
DOI: 10.7554/elife.38869
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation among TRPV1 channels and phosphoinositide 3-kinase in response to nerve growth factor

Abstract: Although it has been known for over a decade that the inflammatory mediator NGF sensitizes pain-receptor neurons through increased trafficking of TRPV1 channels to the plasma membrane, the mechanism by which this occurs remains mysterious. NGF activates phosphoinositide 3-kinase (PI3K), the enzyme that generates PI(3,4)P2 and PIP3, and PI3K activity is required for sensitization. One tantalizing hint came from the finding that the N-terminal region of TRPV1 interacts directly with PI3K. Using two-color total i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 71 publications
(90 reference statements)
0
37
1
Order By: Relevance
“…4B and C). Both PI3K and MAPK activation has been reported to increase the activity of TRPV1 channels by increasing their surface expression (Ma et al, 2017;Stratiievska et al, 2018) but we found no evidence for increased Piezo2 trafficking to the plasma membrane in response to GABAB receptor activation (Fig. S3).…”
Section: Discussioncontrasting
confidence: 52%
“…4B and C). Both PI3K and MAPK activation has been reported to increase the activity of TRPV1 channels by increasing their surface expression (Ma et al, 2017;Stratiievska et al, 2018) but we found no evidence for increased Piezo2 trafficking to the plasma membrane in response to GABAB receptor activation (Fig. S3).…”
Section: Discussioncontrasting
confidence: 52%
“…However, whether EREG enhances TRPV1 activity through mechanisms such as transcriptional regulation, or by enhancing cell surface abundance, remain to be determined (Figure 3A). Similarly, NGF administration has also been reported to promote sensitization in part by inducing TRPV1 upregulation through a PI3K-dependent mechanism (Figure 3B) (Stein et al, 2006;Zhu and Oxford, 2007a;Stratiievska et al, 2018).…”
Section: Phosphatidylinositol 3-kinasementioning
confidence: 88%
“…LPA has been extensively linked to the generation of chronic neuropathic pain through its interactions with G protein-coupled receptors (GPCRs) [89][90][91][92] and to modulate the activity of several ion channels [93][94][95][96][97]. Regulation of the activity of TRPV1 by molecules of a lipidic nature has been explored, and it has been described that PIP 2 [98][99][100][101][102][103][104][105][106], polyunsaturated fatty acids (PUFAs) [107], monounsaturated fatty acids [108] and cholesterol [109][110][111] can modulate the activity of TRPV1, either directly or indirectly. However, reports of direct interactions of LPA with ion channels, in general, are scarce [95,112,113].…”
Section: Lysophosphatidic Acid: a Pain-producing Phospholipidmentioning
confidence: 99%